2022
DOI: 10.3390/ijms23169096
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide (GO): A Promising Nanomaterial against Infectious Diseases Caused by Multidrug-Resistant Bacteria

Abstract: Infectious diseases are major threat due to it being the main cause of enormous morbidity and mortality in the world. Multidrug-resistant (MDR) bacteria put an additional burden of infection leading to inferior treatment by the antibiotics of the latest generations. The emergence and spread of MDR bacteria (so-called “superbugs”), due to mutations in the bacteria and overuse of antibiotics, should be considered a serious concern. Recently, the rapid advancement of nanoscience and nanotechnology has produced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 81 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…(a) Schematic showing antibacterial mechanism of GO. Reprinted with permission from ref . Copyright 2022, MDPI, (no changes).…”
Section: Mechanism Multifunctional Characteristics Of Tio2/go Nanocom...mentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Schematic showing antibacterial mechanism of GO. Reprinted with permission from ref . Copyright 2022, MDPI, (no changes).…”
Section: Mechanism Multifunctional Characteristics Of Tio2/go Nanocom...mentioning
confidence: 99%
“…77,78 The oxidative nature and sharp edges of GO destroy the cell membrane and disrupt its integrity as schematically shown in Figure 4(a). 78,79 Additionally, it is demonstrated that TiO 2 NPs are also extensively researched for antibacterial activity. 33,80 The GO and TiO 2 NPs both generate ROS, which are efficient killers of the majority of bacteria.…”
Section: Fundamentals Of Nanomaterials With Multifunctional Activitie...mentioning
confidence: 99%
“…Large-sized G has strong adsorption potential owing to greater surface energy which leads to the adsorption of the large number of microbial cells on the surface and hence more bacterial cells to be killed [ 34 ]. Furthermore, GO with reduced size displayed strong antibacterial activity in coatings [ 35 , 36 ]. This was predominantly due to the higher number of defects in small-sized sheets that further leads to oxidative-stress-mediated cell death.…”
Section: Introductionmentioning
confidence: 99%
“…As a proof of concept, the bactericidal abilities of these plasma-derived hydrogels containing graphene-related materials were tested. Different mechanisms concerning the bactericidal effect of graphene-based nanomaterials have been proposed in the literature, , which can be summarized in (i) nanoblade effect (membrane cutting and leakage of intracellular components), (ii) wrapping (bacteria wrapped by nanosheets), and (iii) oxidative stress induction (membrane damage via generation of reactive oxygen species). However, as already discussed in the previous sections, GO remains inside the plasma-derived hydrogels, most probably due to its interaction with fibrin polymer chains and its role as a cross-linker agent taking part of the hydrogel structure.…”
mentioning
confidence: 99%